Additional file 6 of Machine learning algorithms to identify cluster randomized trials from MEDLINE and EMBASE - Ahmed A. Al-Jaishi; Monica Taljaard; Melissa D. Al-Jaishi; Sheikh S. Abdullah; Lehana Thabane; P. J. Devereaux; Stephanie N. Dixon; Amit X. Garg (figshare, 2022)
Additional file 6. Python libraries used for this project.
Keywords: Artificial Intelligence and Image Processing